Deviations in criminal filings of child abuse and neglect during COVID-19 from forecasted models: An analysis of the state of Oklahoma, USA. (June 2021) - Whelan, John; Hartwell, Micah; Chesher, Tessa; Coffey, Sara; Hendrix, Amy D.; Passmore, Sarah J.; Baxter, Michael A.; den Harder, Margaret; Greiner, Benjamin
Abstract: Background: The COVID-19 pandemic has contributed to risk factors for child abuse and neglect and disrupted conventional abuse surveillance. Objective: The goal of this study was to assess how counts of criminal charges have been affected by COVID-19 social distancing measures and related policy changes. Participants and Setting: This study used publicly available court filings pertaining to child abuse and neglect from Jan 1, 2010 to June 30, 2020. Methods: Autoregressive integrated moving average (ARIMA) algorithms were constructed with case data from January 2010 to January 2020 to forecast trends in criminal charges for February to June 2020. These forecasted values were then compared to actual charges filed for this time period. Results: Criminal cases filed between February and June 2020, had an overall 25.7 percent lower average than forecasted. All individual months had progressively lower cases than forecasted with the exception of March. June had the largest deviation from forecasted with 60.1 percent fewer cases than predicted. Conclusions: Although risk factors for child abuse have increased due to COVID-19, these findings demonstrate a declining trend in child abuse charges. Rather than a decreasing incidence of child abuse and neglect, it is more likely that less cases are being reported. The results warrant immediate action and further investigation in order to address the dangers this pandemic poses for children in abusive situations.